Interpersonal communication relating to others - Beebe, Steven A.; Beebe, Susan J.; Redmond, Mark V. (Toronto, Ontario Pearson Custom Publising, 2004)
"It's about how to enhance the quality of your interpersonal communication with others. The importance of being other-oriented was the foundation of the first eight well- received editions of Interpersonal Communication: Relating to Others, and it continues to be the central theme of the Thrid edition"--
Keywords: Interpersonal communication